Nanoplasmonics, nano-optics, nanocomposites, and surface studies : selected proceedings of the second FP7 Conference and the third International Summer School Nanotechnology: From Fundamental Research to Innovations, August 23-30, 2014, Yaremche-Lviv, Ukraine /: selected proceedings of the second FP7 Conference and the third International Summer School Nanotechnology: From Fundamental Research to Innovations, August 23-30, 2014, Yaremche-Lviv, Ukraine. (2015) - Unknown
No abstract available